Globalization and treats to national security - M. Kleymenov; I. Kleymenov (Правоприменение)
УДК 343.9.01Subject. The article is devoted to the criminological characteristics of globalization, its im-pact on the criminality of law enforcement.Aim. The aim of the authors is to identify the locations of different types of globalization in the system of criminogenic factors and threats to national security, but also offer criminal legal means of eliminating such threats.Methodology. The authors use methods of criminological analysis, the conceptual apparatus of the interdisciplinary theory of security as well as sociological methods (survey).Results, scope of application. Globalization is an extremely controversial process, that has both positive (anticriminogenic) and negative (criminogenic) sides and the consequences. The contradictory nature of globalization is reflected in the fact that it's an objectively subjective process. The authors note the construction of the myths of globalization in the scientific consciousness. The authors questioned the objectivity of the arguments in favour of corporatization of state unitary enterprises and noted that this process as a manifestation of economic globalization leads to their notable criminalization. The article notes that the conditions for the appropriation of other people's property appears in the process of contemporary economic globalization. Unexpected results of a survey conducted by the authors showed that the possible confiscation of assets of Russian oligarchs is not considered as a security threat by many Russians.Active dissemination of the media significantly expands the possibilities for anticriminogenic information impact on the population in practice. However, this potential is used not enough. Mechanisms of the criminalization of the information space are used much more active by media to manipulate mass consciousness in the interests of the subjects of glob-alization. The authors identified levels of such manipulation and the proposed criminal legal methods to prevent it.Conclusions. National security threats generated by globalization should be eliminated by criminal-legal means.